Imagens: passages and projections - Aranha, Carmen Sylvia Guimarães (Revista ARA, 2020)
Here are presented dialogues revealed in Memorial do Desenho, curatorial research carried out at MAC USP. Drawing is discussed as a fundamental element in the construction of the contemporary image. From the phenomenology of the Merleau-Ponty gaze, motivating aspects are highlighted for the understanding of aesthetic relations of the curatorial and museographic propositions of the exhibition